Sales Performance and Social Preferences - Andrea Essl; Frauke von Bieberstein; Michael Kosfeld; Markus Kröll (Institute of Labor Economics (IZA), 2018)
We use an incentivized experimental game to uncover heterogeneity in otherregarding preferences among salespeople in a large Austrian retail chain. Our results show that the majority of agents take the welfare of others into account but a significant fraction reveals self-regarding behavior. Matching individual behavior in the game with firm data on sales performance shows that higher concern for others is significantly associated with higher revenue per customer. At the same time, it is also associated with fewer sales per day. Both effects offset each other, so that the overall association with total sales revenue becomes insignificant. Our findings highlight the nuanced role of self- vs. other-regarding concerns in sales contexts with important implications for management and marketing research.
Keywords: C91; D91; M31; 330; other-regarding preferences; sales performance; experimental games